О значимости метафизики для человека - Дышкант, Татьяна Николаевна (Національний аерокосмічний університет ім. М. Є. Жуковського "Харківський авіаційний інститут", 2018)
Постмодернизм, претендующий на выражение духа современного общества во всех сферах человеческой деятельности, объявил о наступлении постметафизического времени. Последствия ситуации "преодоления метафизики" и рассматривает данная статья.

Postmodernism, claiming to express the spirit of modern society in all spheres of human activity, announced the advent of post-metaphysical time. This article examines the consequences of the situation of "overcoming metaphysics".
About significance of metaphysics for human
Keywords: сакральная сфера; сознание; целостность; Кант; metaphysics; sacred sphere; consciousness; integrity